2020
DOI: 10.1016/j.scitotenv.2020.139385
|View full text |Cite
|
Sign up to set email alerts
|

First evidence of microplastics in nine lakes across Patagonia (South America)

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(30 citation statements)
references
References 41 publications
3
19
0
8
Order By: Relevance
“…Although much research has been focused on river ecosystems, it has also been shown that plastic pollution also occurs within ponds and lakes across the globe (Eriksen et al 2013;Free et al 2014;Baldwin et al 2016;Vaughan et al 2017;Alfonso et al 2020). For example, in a recent study, Alfonso et al (2020) concluded that microplastic pollution occurs even in lakes located in remote and relatively pristine areas such as the Patagonian Andes which is considered to be one of the most sparsely populated and remote regions of the world.…”
Section: Microplastic and Freshwater Ecosystemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although much research has been focused on river ecosystems, it has also been shown that plastic pollution also occurs within ponds and lakes across the globe (Eriksen et al 2013;Free et al 2014;Baldwin et al 2016;Vaughan et al 2017;Alfonso et al 2020). For example, in a recent study, Alfonso et al (2020) concluded that microplastic pollution occurs even in lakes located in remote and relatively pristine areas such as the Patagonian Andes which is considered to be one of the most sparsely populated and remote regions of the world.…”
Section: Microplastic and Freshwater Ecosystemsmentioning
confidence: 99%
“…Although much research has been focused on river ecosystems, it has also been shown that plastic pollution also occurs within ponds and lakes across the globe (Eriksen et al 2013;Free et al 2014;Baldwin et al 2016;Vaughan et al 2017;Alfonso et al 2020). For example, in a recent study, Alfonso et al (2020) concluded that microplastic pollution occurs even in lakes located in remote and relatively pristine areas such as the Patagonian Andes which is considered to be one of the most sparsely populated and remote regions of the world. However, in contrast to rivers, lakes and ponds are more likely to retain plastic that has been settled in the sediment, without further transport to the ocean, and would therefore likely accumulate plastic over time (Vaughan et al 2017;Horton and Dixon 2018).…”
Section: Microplastic and Freshwater Ecosystemsmentioning
confidence: 99%
“…Microplastics found in freshwater ecosystems can contaminate aquatic biota, cause physical damage, and transfer into the food chain [1,10,11], while toxic effects are assumed to be low [12]. Since the emergence of systematic studies, microplastic pollution has been identified in lakes of different dimensions in North America [13,14], South America [15], Europe [9,16], Asia [17][18][19], and Africa [20]. Despite growing evidence, the terrestrial component of the global microplastic budget is not well understood because sources, stores, and fluxes are poorly quantified [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Aunque actualmente siguen siendo menos los estudios sobre MPs que se centran en ambientes de agua dulce, se sugiere que su abundancia es comparable a los ecosistemas marinos (Klein et al, 2018). Se han registrado MPs en ríos, lagos y estuarios a lo largo de prácticamente todo el planeta (Alfonso et al, 2020b;Blettler et al, 2018;Lima et al, 2014;McCormick et al, 2016). Las cuencas de los ríos y estuarios son considerados como las vías de transporte de MPs desde los continentes hacia los océanos.…”
Section: Mps Presentes En Diversos Ambientesunclassified
“…Por lo que este registro, junto con los del Río de la Plata, suman información acerca de la contaminación por MPs en la cuenca del Plata. Por otro lado, también se cuenta con investigaciones en ambientes lénticos, en las cuales confirman la presencia de MPs en nueve lagos de la Patagonia y en una laguna de la provincia de Buenos Aires (Alfonso et al, 2020a;2020b).…”
Section: Antecedentes Del Tema En Argentinaunclassified